Analisis Kebijakan Kurikulum Merdeka dan Implikasinya Terhadap Kualitas Pendidikan - Rahmafitri, Fadhilah; Deswita, Elvi; Trisoni, Ridwal (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
This article discusses the Analysis of the Merdeka Curriculum Policy and Its Implications on the Quality of Indonesian Education. This policy is a response to global developments and the demands of the times, necessitating a more inclusive, adaptive, and relevant education. The research method employed is library research, which involves examining relevant sources or references to address research problems and find solutions. The research findings indicate that the Merdeka Belajar Policy has significantly and critically impacted the quality of education in Indonesia. It not only makes education more relevant but also aligns Indonesian education with the demands of the times, balancing global and local perspectives to ensure a better quality of education for future generations. The importance of the Merdeka Curriculum in the 4.0 era is emphasized, with a primary focus on enhancing literacy, numeracy, and character development. Concrete findings from this research show that emphasis on these three aspects forms the fundamental basis for improving the quality of education.